Assessment of immobilized cell reactor and microbial fuel cell for simultaneous cheese whey treatment and lactic acid/electricity production - Ghasemi, M. (Elsevier Ltd, 2017)
Two biological methods for treatment of cheese whey and concentrated cheese whey were investigated in this research. As the first method, fermentation of cheese whey for production of lactic acid, in an immobilized cell reactor (ICR) was successfully carried out. The immobilisation of Lactobacillus bulgaricus was performed by the enriched cells cultured media harvested at exponential growth phase. Furthermore, the FTIR analysis has been done to prove the production of lactic acid. The COD removal during the continuous process for both whey and concentrated whey was above 70 which showed the capability of reaction for wastewater treatment. The cells were immobilised by sodium alginate as a perfect polymer in this regard. The maximum produced lactic acid from whey was 10.7 g l−1 at 0.125 h−1 and 19.5 g l−1 from concentrated whey at 0.063 h−1. Finally it can be concluded that the process is efficient for lactic acid production and COD removal simultaneously. As the second studied method, whey and concentrated cheese whey were used as the sources of carbon in a microbial fuel cell. The power densities of 188.8 and 288.12 mW m−2 were recorded for whey-fed and concentrated whey-fed MFCs while the COD removal were 95 and 86 respectively. Biological wastewater treatment can be a very efficient alternative for traditional wastewater treatment which selecting any and or integrating of them depends on specific applications needed to be achieved. © 2016 Hydrogen Energy Publications LLC